Development of a New Hyaluronic Acid Based Redox-Responsive Nanohydrogel for the Encapsulation of Oncolytic Viruses for Cancer Immunotherapy - Siyuan Deng; Alessandra Iscaro; Giorgia Zambito; Yimin Mijiti; Marco Minicucci; Magnus Essand; Clemens Lowik; Munitta Muthana; Roberta Censi; Laura Mezzanotte; Piera Di Martino (Nanomaterials, 2021)
Oncolytic viruses (OVs) are emerging as promising and potential anti-cancer therapeutic agents, not only able to kill cancer cells directly by selective intracellular viral replication, but also to promote an immune response against tumor. Unfortunately, the bioavailability under systemic administration of OVs is limited because of undesired inactivation caused by host immune system and neutralizing antibodies in the bloodstream. To address this issue, a novel hyaluronic acid based redox responsive nanohydrogel was developed in this study as delivery system for OVs, with the aim to protect the OVs following systemic administration. The nanohydrogel was formulated by water in oil (W/O) nanoemulsion method and cross-linked by disulfide bonds derived from the thiol groups of synthesized thiolated hyaluronic acid. One DNA OV Ad[I/PPT-E1A] and one RNA OV Rigvir® ECHO-7 were encapsulated into the developed nanohydrogel, respectively, in view of their potential of immunovirotherapy to treat cancers. The nanohydrogels showed particle size of approximately 300–400 nm and negative zeta potential of around −13 mV by dynamic light scattering (DLS). A uniform spherical shape of the nanohydrogel was observed under the scanning electron microscope (SEM) and transmission electron microscope (TEM), especially, the successfully loading of OV into nanohydrogel was revealed by TEM. The crosslinking between the hyaluronic acid chains was confirmed by the appearance of new peak assigned to disulfide bond in Raman spectrum. Furthermore, the redox responsive ability of the nanohydrogel was determined by incubating the nanohydrogel into phosphate buffered saline (PBS) pH 7.4 with 10 μM or 10 mM glutathione at 37 °C which stimulate the normal physiological environment (extracellular) or reductive environment (intracellular or tumoral). The relative turbidity of the sample was real time monitored by DLS which indicated that the nanohydrogel could rapidly degrade within 10 h in the reductive environment due to the cleavage of disulfide bonds, while maintaining the stability in the normal physiological environment after 5 days. Additionally, in vitro cytotoxicity assays demonstrated a good oncolytic activity of OVs-loaded nanohydrogel against the specific cancer cell lines. Overall, the results indicated that the developed nanohydrogel is a delivery system appropriate for viral drugs, due to its hydrophilic and porous nature, and also thanks to its capacity to maintain the stability and activity of encapsulated viruses. Thus, nanohydrogel can be considered as a promising candidate carrier for systemic administration of oncolytic immunovirotherapy.